2011
DOI: 10.1111/j.1399-3089.2011.00679.x
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia after pig‐to‐baboon liver xenotransplantation: where do platelets go?

Abstract: Following liver xenotransplantation, the early disappearance of platelets from the circulation was at least in part due to their aggregation with circulating WBC, which may augment their deposition in the liver xenograft and native lungs. Prevention of platelet aggregation with monocytes and neutrophils is likely beneficial in reducing their subsequent sequestration in the liver xenograft and native organs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 23 publications
2
35
0
Order By: Relevance
“…In a recent study, high amounts of platelet-platelet and platelet-WBC aggregates were found and linked to low apparent platelet counts. 7,11 In the present study, we also observed platelet-WBC aggregation after 10 and 20 minutes of incubation of whole, non-anticoagulated human blood with PAEC grown on microcarrier beads. These data suggest that platelet aggregation with WBC might be a common phenomenon in pigto-primate xenotransplantation or xenoperfusion.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…In a recent study, high amounts of platelet-platelet and platelet-WBC aggregates were found and linked to low apparent platelet counts. 7,11 In the present study, we also observed platelet-WBC aggregation after 10 and 20 minutes of incubation of whole, non-anticoagulated human blood with PAEC grown on microcarrier beads. These data suggest that platelet aggregation with WBC might be a common phenomenon in pigto-primate xenotransplantation or xenoperfusion.…”
Section: Discussionsupporting
confidence: 64%
“…8 Transplantation of organs from α1,3-galactosyltransferasegene-knockout(GalTKO)orGalTKO and human CD46 transgenic pigs also led to thrombocytopenia throughout the posttransplant period. 11 Determination of the mechanisms responsible for this thrombocytopenia is necessary for the development of preventive strategies. In this study, we have shown the expression of ASGR1, a known platelet binding C-type lectin receptor, in PAEC as well as PFAEC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelet loss and platelet/leukocyte aggregation would appear to be a major problem. 21,39 However, if the native liver remains in situ , the production of primate coagulation factors leads to the development of thrombotic microangiopathy in the graft, resulting in ischemic injury and graft destruction (just as in pig heart and kidney xenografts).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has been presented to indicate that (i) primate platelets are phagocytosed by pig liver macrophages (Kupffer cells) and sinusoidal endothelial cells, 2023,44 or (ii) may be lost in platelet-leukocyte aggregates in the graft and in certain recipient organs. 20,39 …”
Section: Introductionmentioning
confidence: 99%